Slip Control for a Three-Wheeled Electric Motorcycle - Karlin,Andreas (2021)
The aim of this Master Thesis was to design, implement and test a slip controller for an electric three-wheeled motorcycle in order to prevent undesirable slip on the driving wheel during acceleration and regenerative braking. A PI controller was implemented for the two different cases and was tested through various experiments and driving conditions. Three different control strategies were also designed and compared through simulations, a PI, LQR and a MPC controller for both acceleration and braking were designed and tested through five different driving conditions. All three controllers show promising results to control the slip and the implemented PI controller was also able increase safety on slippery surfaces.